1994
DOI: 10.1007/bf00600429
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study and clinical use of poly(vinyl acetate) emulsion as liquid embolisation material

Abstract: A new material, an emulsion of poly(vinyl acetate) was experimentally developed and clinically used to overcome several disadvantages in currently used liquid embolisation materials. The emulsion microparticles, 0.3-0.7 microns in size, possessed cationic charge on the surface and hence aggregated immediately on contact with fluids containing anions. This inert polymer has the advantage that it does not induce a deleterious reaction in living tissue. Moreover, its medium is water and it is not adhesive, like t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Also it was shown that PVAc remained inert in blood vessels. 34 Several patents are registered for novel compositions suitable for use in embolizing blood vessels using biocompatible polymers including PVAc. The composition of these inventions are particularly useful in embolizing blood vessels 35 or they can be applied to intravascular medical devices.…”
Section: Introductionmentioning
confidence: 99%
“…Also it was shown that PVAc remained inert in blood vessels. 34 Several patents are registered for novel compositions suitable for use in embolizing blood vessels using biocompatible polymers including PVAc. The composition of these inventions are particularly useful in embolizing blood vessels 35 or they can be applied to intravascular medical devices.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, newer embolic materials are still being developed and tested (3, 4, 13-16). Embolic materials used in renal vascular lesions include absolute ethanol, ethibloc, gelfoam, polyvinyl alcohol, isobutyl-2-cyanoacrylate, coils, detachable balloons and autologous tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrogels containing functional groups such as COOH usually show good biocompatibility with blood, body fluids, and tissues (Ha et al, 2013). This inert polymer has the advantage that it does not induce a deleterious reaction in living tissue (Sadato et al, 1994). Because of all these characteristics PVAc has been used in many medical fields, including drug and cell carries and in tissue engineering (Abdal-hay et al, 2015).…”
Section: Introductionmentioning
confidence: 99%